Educação Física Compartilhada: possibilidade para inclusão de estudantes com deficiências no contexto escolar - Gatti, Melina Radaelli (Universidade Federal de São Carlos, 2024)
The enrollment of students with disabilities in mainstream schools has progressively increased in recent years. From the perspective of inclusive education, school Physical Education has sought to ensure opportunities for effective participation for the target population of special education. However, there are still many challenges to the inclusion of students with disabilities in the school context, and as a consequence, a large portion remains “functionally” excluded. This has led to an interest in investigating Unified Physical Education and Cooperative Learning in order to develop a Shared Physical Education (SPE) program, which consists of an extracurricular and complementary Physical Education program carried out after school hours, based on principles such as cooperative learning, volunteerism, and peer tutoring strategies as possibilities for the inclusion of students with disabilities in the school context. Thus, the aim of this study was to design, implement, and evaluate a Shared Physical Education program, with a view to the inclusion of students with disabilities in the school context. Specifically, the study sought to analyze SPE as a possibility for the inclusion of students with disabilities in the school environment, and to examine this experience from the perspective of the participants involved, based on a collaborative culture (students, teachers, coordinators, and principals). The study was characterized as a quantitative-descriptive field research focused on program evaluation. Data collection was conducted in two municipal schools in a medium-sized city in the interior of the state of São Paulo, selected by convenience sampling. The participants were: 16 students with disabilities (SWD) from the 6th to the 9th grade; 16 students without disabilities (SND) from the 8th and 9th grades; Physical Education teachers who taught the students participating in the research (n = 3); Special Education Service (SES) teachers from the participating schools (n = 3); school coordinators (n = 2); and school principals (n = 2). The data collection instruments included initial and final semi-structured interviews with all participants; completion of measurement scales by students with and without disabilities during the implementation of the Unified Physical Education (UPE) program; and field diaries and an observation guide completed by the researcher during the program implementation. Data analysis was based on thematic analysis. The results were divided into three sections: Section I – descriptive aspects of the program, including recruitment, training, and implementation of the UPE program; Section II – evaluation of the UPE program based on the instruments used; and Section III – analysis of the interviews. It was observed that, in both schools, students without disabilities initially had difficulty providing the necessary assistance to students with disabilities due to a lack of proximity between students, the configuration of class structure and dynamics, and shyness in exposing themselves. Throughout the interventions, the bond between students increased: students without disabilities began to offer types of support in a more natural and appropriate manner, while students with disabilities started to request less assistance to perform activities. It is concluded that it was possible to design and implement the SPE program, and it was found that the program enhanced social skills and promoted positive transformations in interpersonal relationships, bringing benefits to the development and learning of all students, thus proving to be a promising inclusion strategy. However, challenges such as family involvement and the need for resources and school investment remain.
Shared Physical Education: a possibility for the Inclusion of students with disabilities in the school context
Keywords: Educação Física Escolar; Educação Especial; Educação Inclusiva; Pessoas com deficiência; School Physical Education; Special Education; Inclusive Education; People with Disabilities; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; 4. Educação de Qualidade